Melindungi Keraton Surosowan pada Masa Perang dengan Blue Shield Emblem - Vitrana, Mokhamad Gisa; Oktavianus, Afriman; Hanifah, Amiratul Aulia; Oktrian, Pryanka Ceza (Hang Tuah Law Journal, 2025)
Deliberate destruction of cultural heritage with outstanding universal value during war is an international crime. While efforts to protect cultural heritage in wartime have been coordinated through the 1954 Hague Convention with its Blue Shield Emblem, numerous cultural sites have still been destroyed in the last decade. This issue is compounded by the varying implementation of these prtections among states. Despite Indonesia ratifying the Convention in 1966, it has struggled to properly implement the Blue Shield Emblem for its cultural heritage sites. No country is entirely safe to the risk of war, especially given the increasing conflicts in recent years. This research examines the challenges of applying the Blue Shield Emblem to the Surosowan Palace, a significant cultural heritage site in Serang City, Indonesia. The Surosowan Palace holds historical value as a symbol of the Indonesian national identity, particularly as the Banten Kingdom was a vital trading hub in Southeast Asia from the 14th to the 17th centuries. This study uses a socio-legal method, drawing on data from interviews with key informants, to explore the barriers and gaps in protecting Surosowan Palace. This research highlights Indonesia's need for regulatory adjustments to implement the 1954 Hague Convention and emphasizes the inclusion of Surosowan Palace as a Blue Shield Emblem cultural heritage site.